Women in Management in STEM: Which Factors Influence the Achievement of Leadership Positions? (International Journal of Gender, Science and Technology, 2020)
Efforts to inspire women to enter a STEM-related profession continue to increase. However, even though many women are now working in these male-dominated professions, they are not always successful. This is especially the case in higher management positions, where women are confronted with gender-specific barriers. We discuss here some of the factors that can increase the probability of women finding success in their profession.This study examines the individual factors that favor the career development of women in STEM. Our main research question is: which factors influence the achievement of leadership positions for women in STEM? We developed an online survey addressing several professional associations in the STEM fields to answer this question. Logistic regression factors were used to predict these women’s achievement of leadership positions.Significant effects are noted in the women’s work motivation, career orientation and area of expertise. Positive influencing factors include high intrinsic work motivation, orientation towards general management and autonomy, and working in the field of architecture. Our findings show that children are not an obstacle to a woman’s career path in the STEM professions and that male role models are a beneficial factor to women who seek to reach leadership positions.